2019
DOI: 10.1007/s12253-019-00620-5
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on Selected Markers of Oxidative Stress, Inflammation and Angiogenesis in Patients with Bladder Cancer

Abstract: In recent years, bladder cancer (BC) has been reported as one of the most commonly occurring cancers among older people, and its detection is still difficult. Therefore, there is a need to search for additional useful markers of disease. Some studies indicate the important roles of inflammation and oxidative stress (OS) in bladder tumour pathogenesis. The aim of this study was to examine the levels of selected markers of OS, inflammation and angiogenesis in blood plasma/serum samples derived from patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 40 publications
4
16
2
1
Order By: Relevance
“…The MDA serum level reflects free-radical cell damage. The results of our study showed that the MDA serum level in Ta, T1, and T2-T4 group was significantly higher than the MDA level in the control group, a finding compatible with the results of several studies [12][13][14][15][16][17][18][19]. The MDA levels of the patients in T1 and T2-T4 groups were significantly higher than in the Ta group, whereas the MDA serum levels between the T1 and T2-T4 groups were not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The MDA serum level reflects free-radical cell damage. The results of our study showed that the MDA serum level in Ta, T1, and T2-T4 group was significantly higher than the MDA level in the control group, a finding compatible with the results of several studies [12][13][14][15][16][17][18][19]. The MDA levels of the patients in T1 and T2-T4 groups were significantly higher than in the Ta group, whereas the MDA serum levels between the T1 and T2-T4 groups were not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
“…ROC curve analysis suggested that serum MDA levels could serve as a potential biomarker in the differentiation of cancer grade, as well as cancer progression potential. A recent study performed by Sawicka et al showed that serum MDA level had the highest growth in the G3 group compared with controls, and among Ta, T1, and T2, the MDA level increased against the control by a similar percentage [17]. Unlike this, Yalcin et al reported the growth of MDA concentrations among G1 and G2 patients [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipids are major components of cell membranes and play an important role in cell membrane stabilization and signal transduction [ 12 ]. Lipid peroxidation defined as oxidative deterioration of polyunsaturated fatty acids (PUFAs), is a process, which can damage DNA and help in cancer development [ 13 ]. Reactive aldehydes such as 4-hydroxy-2-nonenal, acrolein, and malondialdehyde (MDA), can affect cell proliferation through formation of DNA-DNA or DNA-protein crosslinks, which can result in replication errors, mutations and genomic instability, if not repaired before DNA replication process [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of total SH concentration reflects the antioxidant capacity of blood plasma, but it is also a good indicator of oxidative damage to proteins in different diseases such as diabetes mellitus, metabolic syndrome, cancers, fertility disorders and others. Additionally it is applied as a marker of exposure to certain xenobiotics [1,5,6,7]. Estimating the biochemical and health effects of exposure to different xenobiotics is very important but relatively difficult due to chronic exposure, the low, often subminimal concentrations of xenobiotics, and their different sources as well as their multi-faceted mechanisms of action [8,9].…”
Section: Introductionmentioning
confidence: 99%